THE ROLE OF MODERN EDUCATIONAL TECHNOLOGIES IN IMPROVING THE QUALITY OF EDUCATION (Universal International Scientific Journal, 2026)
This article analyzes the role of modern educational technologies in improving thequality and effectiveness of education. In particular, it examines the opportunities provided by digitalplatforms, interactive methods, and distance learning in individualizing the learning process,developing students’ independent thinking, and improving assessment systems. The impact ofinnovative approaches on the pedagogical process and their practical significance are alsosubstantiated.
Keywords: modern educational technologies; quality of education; innovative approach